Levels and Profile of Tetrodotoxins in Spawning Cephalothrix mokievskii (Palaeonemertea, Nemertea): Assessing the Potential Toxic Pressure on Marine Ecosystems - Grigorii V. Malykin; Peter V. Velansky; Timur Yu. Magarlamov (Toxins)
The ribbon worms of the closely related species Cephalothrix simula, Cephalothrix cf. simula, and Cephalothrix mokievskii, representing the C. simula species complex, possess high concentrations of tetrodotoxin (TTX) and its analogues in all developmental stages from eggs to adults. It has recently been suggested that the eggs and larvae of these animals can be a source of tetrodotoxins (TTXs) for other aquatic organisms. In the current study, TTXs in mature and post-spawning individuals and in the eggs of C. mokievskii were identified using high-performance liquid chromatography–tandem mass spectrometry. For the first time, the quantity and profile of TTXs that these nemerteans released into the environment during spawning were estimated. We showed that the spawning C. mokievskii females released significant amounts of TTX and 5,6,11-trideoxyTTX with their eggs; these levels were sufficient for the potential toxification of marine bioresources. The issues surrounding the monitoring of TTXs in commercial marine animals, and collecting at the sites of the spawning of nemerteans from the C. simula species complex, are discussed.